2000
DOI: 10.1103/physreve.62.4043
|View full text |Cite
|
Sign up to set email alerts
|

Alternans and the onset of ventricular fibrillation

Abstract: Ventricular fibrillation (VF) remains a major cause of death in the industrialized world. Alternans (a period-doubling bifurcation of cardiac electrical activity) have recently been causally linked to the progression from ventricular tachycardia (VT) to VF, a more spatiotemporally disorganized electrical activity. In this paper, we show how alternans and thus VT degenerate to chaos via multiple, specific dynamical routes, largely associated with spatial components of VF dynamics, explaining failures of many re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 52 publications
3
26
0
Order By: Relevance
“…In [35] a nonlocal partial differential equation has been proposed to study spatiotemporal dynamics of alternans. It would be interesting for further studies to see how the transition to conduction blocks explored in these paced cardiac excitable media [34,35,36,37] can be described by the spatially inhomogeneous pitch-fork bifurcation we found in our normal form. The pitchfork bifurcation however does not require a fixed pacing site and does not require external pacing but rather is dynamically induced.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [35] a nonlocal partial differential equation has been proposed to study spatiotemporal dynamics of alternans. It would be interesting for further studies to see how the transition to conduction blocks explored in these paced cardiac excitable media [34,35,36,37] can be described by the spatially inhomogeneous pitch-fork bifurcation we found in our normal form. The pitchfork bifurcation however does not require a fixed pacing site and does not require external pacing but rather is dynamically induced.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…To go beyond the case of a single pulse circulating in a ring, periodically stimulated excitable media have been studied in the context of alternans [41,42,35,34,36,37]. In [41,36] one-dimensional maps were developed to study the Hopf bifurcation and the transition to conduction blocks.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 2 decades, experimental, theoretical, and clinical studies have identified mechanistic and statistical relations linking this phenomenon to a heightened risk of arrhythmogenesis. 1,2 In a guinea pig model, TWA led to initiation of ventricular fibrillation through a sequence of events that included the presence of spatially discordant (out-of-phase) TWA, unidirectional block of impulse propagation, and reentry. 3 In a canine model of acute ischemia, TWA heralded the first step of a cascade of repolarization instabilities culminating in ventricular fibrillation.…”
mentioning
confidence: 99%
“…Works in a somewhat different line have shown that applying fundamental principles of nonlinear physics, it is possible to forecast beforehand the cardiac disarray arising due to rapid heart rates (ventricular tachycardia (VT)) [11] or that due to aperiodic beating of the heart (ventricular fibrillation (VF)) [11,12]. Of the wide range of possibilities for their origin, researches have been focussed on the transition from tachycardia to fibrillation, generating spiral waves [13,15,16] to the anisotropic nature of ventricles [14] leading to faster electrical propagation parallel to the long axis of muscle fibers. The different methods of electrical defibrillation which have been presently proposed [15,18,19] bear testimony to the intense efforts on arriving at medical solutions from theoretical studies of bio-systems.…”
Section: Introductionmentioning
confidence: 99%